1992
DOI: 10.1002/polb.1992.090300813
|View full text |Cite
|
Sign up to set email alerts
|

Effect of methyl substituents on permeability and permselectivity of gases in polyimides prepared from methyl‐substituted phenylenediamines

Abstract: Permeability and solubility coefficients for H2, CO2, O2, CO, N2, and CH4 in polyimides prepared from 6FDA and methyl‐substituted phenylenediamines were measured to investigate effects of the substituents on gas permeability and permselectivity. The methyl substituents restrict internal rotation around the bonds between the phenyl rings and the imide rings. The rigidity and nonplanar structure of the polymer chain, and the bulkiness of methyl groups make chain packing inefficient, resulting in increases in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
171
2
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 243 publications
(190 citation statements)
references
References 18 publications
14
171
2
1
Order By: Relevance
“…The polyimide bearing 6FDA has an expected higher FFV value due to the bulky −C(CF 3 ) 2 − units as compared with the polyimide derived from BTDA. It is interesting to compare the FFVs of PI-TB-1, prepared from 6FDA and DPD and polymerized using the TB method, with a typical polyimide PI-6FDA-DPD (6FDA-pDiMPD 34 ) polymerized in the normal manner from 6FDA and DPD. The PI-TB-1 showed a significantly higher FFV value (FFV = 0.223) induced by the incorporation of TB units compared with that of PI-6FDA-DPD (FFV = 0.175 34 ).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 3 more Smart Citations
“…The polyimide bearing 6FDA has an expected higher FFV value due to the bulky −C(CF 3 ) 2 − units as compared with the polyimide derived from BTDA. It is interesting to compare the FFVs of PI-TB-1, prepared from 6FDA and DPD and polymerized using the TB method, with a typical polyimide PI-6FDA-DPD (6FDA-pDiMPD 34 ) polymerized in the normal manner from 6FDA and DPD. The PI-TB-1 showed a significantly higher FFV value (FFV = 0.223) induced by the incorporation of TB units compared with that of PI-6FDA-DPD (FFV = 0.175 34 ).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…It is interesting to compare the FFVs of PI-TB-1, prepared from 6FDA and DPD and polymerized using the TB method, with a typical polyimide PI-6FDA-DPD (6FDA-pDiMPD 34 ) polymerized in the normal manner from 6FDA and DPD. The PI-TB-1 showed a significantly higher FFV value (FFV = 0.223) induced by the incorporation of TB units compared with that of PI-6FDA-DPD (FFV = 0.175 34 ). Out-of-plane WAXD measurements were conducted to investigate polymer interchain packing in membranes (Figure 3).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been found that restriction of both packing efficiency and chain mobility may increase gas permeability with minimum permselectivity losses. Families of polycarbonates [3][4][5][6][7][8][9], polysulfones [4,[10][11][12][13][14][15][16][17], polyimides [18][19][20][21][22][23][24][25], polyoxydiazoles and polytriazoles [26,27], aromatic polyesters [28][29][30][31][32], and methyland phenyl-substituted polyphenylene ethers [33,34], have been optimized using these guidelines. Work has been reported showing that the substitution of hydrogen atoms by methyl groups in the four symmetrical ring positions of bisphenol A leads to polycarbonates, polysulfones and polyarylates that are about four times more permeable to gases than the corresponding unsubstituted materials without losing permselectivity [33].…”
Section: Introductionmentioning
confidence: 99%